PERAN APARATUR DESA DALAM PENGELOLAAN KEUANGAN DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 DI DESA LUBUK JAWI KECAMATAN BALAI JAYA KEBUPATEN ROKAN HILIR PROVINSI RIAU - Sagopi Ria Apriliani Juniansen; Gusnardi Gusnardi; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the role of village apparatus in Lubuk Jawi Village, Balai Jaya District, Rokan Hilir Regency, Riau Province in village financial management based on the Minister of Home Affairs Regulation Number 20 of 2018. This research is a quantitative descriptive type of research. Primary data were obtained from five Lubuk Jawi Village apparatus. Data were collected using documentation techniques, in-depth observation, and interviews. The results showed that the percentage of answers from the five informants on the planning aspect reached 95% including in the very role category, in the implementation aspect reaching 80% including in the role category although there are still some procedures that are still not in accordance with the regulations, in the aspects of administration, reporting, and accountability up to 100% is included in the very important category. The results of the discussion show that the role of village apparatus in the aspects of planning, implementation, administration, reporting and accountability is in accordance with the procedures of the Minister of Home Affairs Regulation Number 20 of 2018 concerning village financial management.Key Words: Village Financial Management, Role of Village Apparatus, Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management